العراقية Bos indicus والأبقار Camelus dromedariues دراسة نسجية مقارنة لكبد الإبل - قاسم سكرضمياء; عبد علي الشمريهيفاء; جاسم الطهطه (University of Thi-Qar Journal of Science, 2019)
The camel liver is highly lubulation in comparative with liver cows , so this study show highly significant difference between the two species in the size of the hepatocytes and their nuclei . the hepatocytes & nucleus in camel liver is very polyhedrale and large than that in cow liver which is more arrange .the diameter of sinusoid in cow liver is larger than that in camel